Quality of Living and Dying: Pediatric Palliative Care and End-of-Life Decisions in the Netherlands - Brouwer, Marije (Cambridge quarterly of healthcare ethics, 2018)
In 2002, The Netherlands continued its leadership in developing rules and jurisdiction regarding euthanasia and end-of-life decisions by implementing the Euthanasia Act, which allows euthanasia for patients 12 years of age and older. Subsequently, in 2005, the regulation on active ending of life for newborns was issued. However, more and more physicians and parents have stated that the age gap between these two regulations—children between 1 and 12 years old—is undesirable. These children should have the same right to end their suffering as adults and newborn infants. An extended debate on pediatric euthanasia ensued, and currently the debate is ongoing as to whether legislation should be altered in order to allow pediatric euthanasia. An emerging major question regards the active ending of life in the context of palliative care: How does a request for active ending of life relate to the care that is given to children in the palliative phase? Until now, the distinction between palliative care and end-of-life decisions continues to remain unclear, making any discussion about their mutual in- and exclusiveness hazardous at best. In this report, therefore, we aim to provide insight into the relationship between pediatric palliative care and end-of-life decisions, as understood in the Netherlands. We do so by first providing an overview of the (legal) rules and regulations regarding euthanasia and active ending of life, followed by an analysis of the relationship between these two, using the Dutch National Guidelines for Palliative Care for Children. The results of this analysis revealed two major and related features of palliative care and end-of-life decisions for children: (1) palliative care and end-of-life decisions are part of the same process, one that focuses both on quality of living and quality of dying, and (2) although physicians are seen as ultimately responsible for making end-of-life decisions, the involvement of parents and children in this decision is of the utmost importance and should be regarded as such.